Employee Engagement and Productivity Mediate the Impact of Transformational Leadership and OCB on The Board of Commissioners of Bawaslu’s Performance - Maulana, Anditya Sentana; Irianto, Jusuf (RSF Conference Series: Business, Management and Social Sciences, 2023)
The success and performance of an organization are determined by the quality of its human resources. An organization can achieve success through good performance, which begins with improving the quality of human resources. The purpose of this research is to understand the impact of each variable. The sample used in this study is nonprobability sampling with purposive sampling techniques. Therefore, the researcher can select samples based on specific criteria, namely the commissioners of the East Java Regional Election Supervisory Body (Bawaslu Jawa Timur), with 65 respondents. There are many results from this study that support the hypothesis, only Employee Engagement does not have a significant effect. This causes the variables through Employee Engagement to have no significant effect.